2018
DOI: 10.1007/s11162-018-9498-y
|View full text |Cite
|
Sign up to set email alerts
|

Do Students with Varying Academic Ability Benefit Equally from Personal Qualities? Applying a Trait and State Perspective

Abstract: Using multilevel models, this study examined whether students with varying academic ability benefit equally from perseverance and intellectual curiosity in terms of academic achievement. In addressing this question two perspectives were applied: a trait perspective, focusing on differences between students, and a state perspective, focusing on differences within students across semesters. By means of an online questionnaire, undergraduate students (N = 2272) were asked to rate themselves on perseverance and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…Our findings demonstrated that competence could be positively transmitted through a specific psychological resourcepsychological capital. This finding was consistent with the prior research on psychological capital, which had demonstrated that psychological capital as an important psychological resource could promote the positive academic outcomes of postgraduate students [59,60]. Moreover, this result was in line with the job demands-resources model, which suggested that individuals could use their resources to deal with different challenges and meet academic research demands to achieve academic outcomes [61].…”
Section: Mediating Effect Of Psychological Capitalsupporting
confidence: 90%
“…Our findings demonstrated that competence could be positively transmitted through a specific psychological resourcepsychological capital. This finding was consistent with the prior research on psychological capital, which had demonstrated that psychological capital as an important psychological resource could promote the positive academic outcomes of postgraduate students [59,60]. Moreover, this result was in line with the job demands-resources model, which suggested that individuals could use their resources to deal with different challenges and meet academic research demands to achieve academic outcomes [61].…”
Section: Mediating Effect Of Psychological Capitalsupporting
confidence: 90%
“…Additionally, increased competition in various aspects of society may contribute to this phenomenon. Nowadays, academic achievement is often assessed solely based on grades and numbers, without considering the individual potential and capabilities of students (Kool et al, 2018). This trend encourages rote memorization over understanding, which represents a lower level of cognitive development.…”
Section: Resultsmentioning
confidence: 99%
“…It deserves to be noted further that grit covering the two subconstructs of perseverance and passion can be nurtured over time from adolescence ( 42 ) to continued academic study ( 43 , 44 ) and work-based learning ( 42 ). The education curriculum on the recognition and management of stress has been verified to increase medical trainees’ perseverance subscales of grit in clerkships ( 45 ).…”
Section: Discussionmentioning
confidence: 99%